2017
DOI: 10.1021/acs.orglett.6b03888
|View full text |Cite
|
Sign up to set email alerts
|

Merging Photoredox with Copper Catalysis: Decarboxylative Alkynylation of α-Amino Acid Derivatives

Abstract: A novel and efficient decarboxylative alkynylation of N-(acetoxy)phthalimides of α-amino acids with terminal alkynes has been developed by merging photoredox with copper catalysis at room temperature, and the reaction provided the valuable propargylamines in good to excellent yields with assistance of [Ru(bpy)]Cl/CuI and visible light. The simple protocol, mild reaction conditions, and high efficiency of this method make it an important strategy for synthesis of diverse molecules containing amino acid fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 97 publications
1
38
0
1
Order By: Relevance
“…For example, the oxidative decarboxylation of aliphatic acids to form alkyl radicals with subsequent capture by alkynyl electrophiles. [14] Concurrent with these studies, Fu reported on the coupling of terminal alkynes with α-amino NHP esters [15] and Baran reported on the coupling of N -hydroxytetrachlorophthalimide (TCNHPI) esters with alkynylzinc or magnesium reagents. [16] Our proposed approach would avoid the need for organometallic reagents and the more expensive TCNHPI [17] without being limited to α-amino acid derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the oxidative decarboxylation of aliphatic acids to form alkyl radicals with subsequent capture by alkynyl electrophiles. [14] Concurrent with these studies, Fu reported on the coupling of terminal alkynes with α-amino NHP esters [15] and Baran reported on the coupling of N -hydroxytetrachlorophthalimide (TCNHPI) esters with alkynylzinc or magnesium reagents. [16] Our proposed approach would avoid the need for organometallic reagents and the more expensive TCNHPI [17] without being limited to α-amino acid derivatives.…”
mentioning
confidence: 99%
“…[16] Our proposed approach would avoid the need for organometallic reagents and the more expensive TCNHPI [17] without being limited to α-amino acid derivatives. [15] Although this approach would use alkyne electrophiles, bromoalkynes [7] are more easily prepared than ethynylbenziodoxolones [18] or alkynyl sulfones. [14a–c] …”
mentioning
confidence: 99%
“…However, acetophenone itself was partially consumed by transamination to 1phenethylamine (entry 25). α,β-Unsaturated ketones (entries [14][15][16][17][18][19][20][21][22][23][24], in particular the derivatives of 2-cyclohexen-1-one (entries 18-21 and 23), are among the most active organocatalysts: for instance, 2 a was produced in > 85 % yield within 4 h by using isophorone or 3-phenyl-2-cyclohexen-1-one. These catalysts increased the amine yield at least by a factor 10 compared to the thermal reaction.…”
Section: Decarboxylation Of Amino Acids To Aminesmentioning
confidence: 99%
“…[18] Decarboxylation is also a step in several photoredox-based carbon-carbon bondforming reactions using protected amino acids as a coupling partner. [19][20][21][22][23] Transition metal-free approaches for amino acid decarboxylation have been reported as well. For instance, the formation of biogenic amines in food and beverages is related either to the presence of carbohydrate-or lipid-derived reactive carbonyl compounds, [24,25] or to the action of amino acid decarboxylases containing pyridoxal 5'-phosphate (PLP) or a pyruvoyl group as cofactor.…”
Section: Introductionmentioning
confidence: 99%
“…Photoredox chemistry has been applied to generate alkyl radicals from alkyl redox-active esters for subsequent Michael addition reactions 35,36 , while a similar approach for decarboxylative alkynylation of α -amino acid derivatives has been used 37 . In view of the difficulty in activating redox-active esters by metal amides, we envisioned a synergetic photoredox and metal catalysis for C-N coupling of redox-active esters with anilines (Fig.…”
mentioning
confidence: 99%